Optimization of Ethylene Oligomerization Process Based on Genetic Algorithms - Antipina, Evgenia; Mustafina, Svetlana; Antipin, Andrev (International Russian Automation Conference (Online), 2024)
The paper is devoted to the development of a genetic algorithm for finding the optimal values of control parameters of the ethylene oligomerization process. The formulation of the problem of optimal control of the ethylene oligomerization process is given. The control parameters are temperature and reaction duration, the values of which are subject to constraints. It is proposed to search for the solution of the formulated problems using a genetic algorithm with real coding. The principle of operation of genetic algorithms is based on the imitation of the processes of evolution of living nature. It includes cyclic application of selection, crossing, mutation and renewal operations to a population of individuals. For each of the problems under consideration the method of representation of the mathematical analog of the population, on the basis of which the solution is searched, is described. A step-by-step genetic algorithm for solving the formulated optimal control problems is given. A computational experiment is carried out, as a result of which the optimal reaction temperature and process duration, at which the target functional takes the largest value, are calculated.